2015
DOI: 10.1186/s12903-015-0112-9
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and biocompatibility of an injectable calcium-silicate-based root canal sealer: in vitro and in vivo study

Abstract: BackgroundThe aim of this study was to investigate the physical properties and biological effects of an experimentally developed injectable premixed calcium-silicate root canal sealer (Endoseal) in comparison with mineral trioxide aggregate (MTA) and a resin-based sealer (AHplus).MethodsThe pH, solubility, dimensional change, flow, and radiopacity of the materials were evaluated. Biocompatibility was evaluated on the basis of cell morphology and a viability test using MC3T3-E1 cells. For evaluate inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
101
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(144 citation statements)
references
References 38 publications
(27 reference statements)
9
101
2
6
Order By: Relevance
“…Devido às excelentes propriedades físico-químicas e biológicas do MTA, novos materiais compostos pelo agregado trióxido mineral surgiram recentemente. [13][14][15][16] Contudo as diversas composições diferentes e as proporções distintas de MTA nas formulações promovem resultados de citotoxicidade variados a estes cimentos com o mesmo componente base. 14,17 O MTA Fillapex foi o material que apresentou a maior citotoxicidade em valores absolutos em todas as diluições e entre todos os cimentos endodônticos testados.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Devido às excelentes propriedades físico-químicas e biológicas do MTA, novos materiais compostos pelo agregado trióxido mineral surgiram recentemente. [13][14][15][16] Contudo as diversas composições diferentes e as proporções distintas de MTA nas formulações promovem resultados de citotoxicidade variados a estes cimentos com o mesmo componente base. 14,17 O MTA Fillapex foi o material que apresentou a maior citotoxicidade em valores absolutos em todas as diluições e entre todos os cimentos endodônticos testados.…”
Section: Discussionunclassified
“…21 Diversos métodos vêm sendo utilizados a fim de avaliar os efeitos citotóxicos dos cimentos endodônticos. 5,9,[11][12][13][14][15][16][17] No presente estudo, a viabilidade celular foi determinada através do ensaio de MTT, que é baseado na habilidade das enzimas desidrogenases mitocondriais, presentes nas células vivas, em converter o sal amarelo tetrazólio para cristais de formazan lilás. As vantagens deste método são sua simplicidade, velocidade, precisão e elevada reprodutibilidade.…”
Section: Discussionunclassified
“…Also, property of flow allows a sealer to penetrate into the irregularities and accessory canals of the root canal system. In the aforementioned study by Lim et al, 2 EndoSeal containing small particles of calcium silicate showed significantly higher flow values compared with the resin-based sealers. However, if the flow is excessive, the risk of sealer extrusion beyond apical foramen is increased, which could damage periodontal tissues or important anatomical structures, such as inferior alveolar nerve or maxillary sinus.…”
Section: Ijoprdmentioning
confidence: 99%
“…1 Endodontic sealers are used for the obturation of root canal systems in order to achieve a fluid-tight seal between the dentinal wall and core-filling material throughout the entire canal. 2 Commercially available various sealers are categorized according to chemical components: Zinc-oxide eugenol, calcium hydroxide-containing, resin-based, glassionomer-based, silicone-based, and newer generation bioceramic-based sealers. 3 As root canal sealers are placed in close contact with the surrounding soft and hard tissues for a long period CASE REPORT 10 EndoSeal (Maruchi, Korea) is a premixed and injectable endodontic sealer that uses moisture in the air to initiate the setting reaction.…”
Section: Introductionmentioning
confidence: 99%
“…16 The greater fracture resistance values obtained for Endoseal MTA in the present study can be attributed to its higher flow rates and biomineralization of dentinal tubules. 17 Lim et al reported that Endoseal MTA exhibited significantly higher flow compared to AH Plus sealer. Endoseal MTA is a premixed material supplied in syringes and the freshly extruded mix exhibits thixotropic behavior.…”
mentioning
confidence: 99%